(3CMcGe GdfLhes - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3EJUGd GdbeQ HGdchGcH ef GdHQhL GdEKfi YTQ, aChd Pdc EJUGdg HRMd ai HQL GdMed ef (B( (3S(B) (3jOd Ydi bhI CUMGH GdUfGFY hXghQ GdNjQ hXdeI GdghGA s
(3BNQgG (B:s
(3W Q jOd Ydi fcO GdYGeI hGdTQcGA hGdVeGf , hge GdeRGQYhf hCQHGH GdejGg hGdadGMhf , hYSQ GdhdGOI hSbhW GdCLfI hehJ aj GdCWaGd hGddg JYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B252 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B397 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs